THE OVERVIEW OF HEMOGLOBIN LEVELS WITH CYANMETHEMOGLOBIN METHOD AND VOLUMETRIC IMPEDANCE IN PATIENTS EXPOSED TO MOSQUITO REPELLENT SPRAY - Andy Setiawan Widodo (Akademi Kesehatan John Paul II Pekanbaru, 2022)
This study aims to determine differences in the results of hemoglobin levels of people exposed to mosquito repellent spray examined using Cyanmethemoglobin and Volumetric Impedance methods. This study employed a cross sectional design. The sample in this study amounted to 30 patients at Pandak 2 Primary Health Center Bantul. The data used secondary data obtained at Pandak 2 Primary Health Center Laboratory, Bantul. The data processing stages carried out in this study were editing, coding, and tabulating which would then the data was analysed using Independent sample T test. The Cyanmethemoglobin method showed that there were 11 patients with normal hemoglobin levels and the remaining 19 patients showed hemoglobin levels below normal, while the Volumetric Impedance method revealed 13 patients with normal hemoglobin levels and the remaining 17 patients showed hemoglobin levels below normal. Based on the results of the T sample Independent Test, there was no significant difference between the Cyanmethemoglobin and Volumetric Impedance methods in the examination of hemoglobin levels in patients exposed to mosquito repellent spray.